Management and outcomes of thoracic sarcomas - a collaboration between Orthopaedic Oncology and cardiothoracic surgery: seven-year clinical data from a tertiary referral centre - Zaid Ahmed Shamsi; Vlad Paraoan; Chang Kim; Sarah Raihanah Saifuddin; Thomas D A Cosker; Duncan Whitwell; Christopher L M H Gibbons; Dionisios Stavroulias; Francesco DiChiara (Journal of Cardiothoracic Surgery)
Abstract Introduction Sarcomas are rare cancers originating from mesenchymal tissues, manifesting in diverse anatomical locations, but notably in connective tissue, muscles and the skeleton. Thoracic sarcomas present a unique diagnostic and surgical challenge attributable to their rarity and pathoanatomy. Standard practice currently comprises wide surgical excision, often accompanied by adjuvant chemotherapy and/or radiotherapy. This approach necessitates a multidisciplinary team, ideally in specialised cancer centres. The Oxford Bone and Soft Tissue Tumour Service is one such centre, and routinely treats such cancers through collaboration between orthopaedic oncology and cardiothoracic surgeons, as well as members of the wider MDT. This study reports the current management and outcomes of primary thoracic sarcoma patients at the Oxford Sarcoma Service over a seven-year period. Objectives Given the rarity of thoracic sarcomas, and their associated diagnostic and management complexities, our aim is to report on the treatment strategies and outcomes of primary thoracic sarcoma patients treated at the Oxford Sarcoma Service from 2017 to 2023. Methods Data pertaining to all thoracic sarcoma cases discussed in multidisciplinary meetings at the Oxford tertiary centre from 2017 to 2023 were retrieved from the local electronic database. These were analysed using appropriate statistical tests to determine significance of the various observations made. Results Of 113 identified cases, chondrosarcoma emerged as the most prevalent histological subtype among 22 distinct varieties. 58% of cases exhibited high-grade features. 32 sarcoma-related deaths occurred, with a mean time from diagnosis to death of 23.16 months. A notable association was observed between high-grade sarcomas and mortality (p = 0.0280). Surgical resection was performed in 77 cases, with 49% of these undergoing surgical resection alone i.e. the patient received no radio- or chemotherapy. Both surgical intervention (p < 0.0001) and clear margins (p = 0.0051) were significantly linked to improved survival. Local recurrence was noted in 28.6% of the 77 surgical cases, and predominantly in the high-grade sarcomas (81.8%). However, no statistical association was found between recurrence and margin status in our data. Conclusion Our results indicate that primary resection remains the cornerstone of thoracic sarcoma treatment, representing the single strongest independent factor for survival in treatable cases. Variability in outcomes and overall survival likely stems from factors such as histological diversity, predominance of high-grade sarcomas, and wide age range at diagnosis. Ongoing prospective database update and collaborative efforts across centres would further clarify prognoses and recommendations for specific tumours, based on observational data.